Gambaran Pengetahuan Dan Sikap Remaja Putri Dalam Menangani Dismenore Di SMA Airlangga Namu Ukur Tahun 2021 - P, Indra Hizkia; Imelda Sirait, Imelda Sirait; Ginting, Kristin Febriani Br (JOURNAL OF HEALTH SCIENCE, 2025)
Adolescence is a very important developmental period, and begins with the maturation of the physical (sexual) organs so that they are able to reproduce, including puberty in adolescent girls, namely menstruation, with symptoms that often occur are discomfort during menstruation and even severe pain called dysmenorrhea. . This study aims to describe the knowledge and attitudes of young women in dealing with dysmenorrhea at Airlangga Namuukur High School in 2021. The type of research is descriptive research. The population of the study was 44 students of SMA Airlangga Namuukur class X and XI with total sampling technique. The results showed that most of the young women with good knowledge were 40 people (90.9%) and had sufficient knowledge as many as 4 people (9.1%) and the attitude in dealing with dysmenorrhea was mostly positive 26 people (59.1) and 18 people negative attitude (40.95%).